The problem of safe obstetrical care - Salazar Marzal, Ego (2019)
The problem of safe obstetrical care has special relevance in recent years due to the interest of health professionals in reducing adverse events and improving healthcare. However, this is pursued in complex, uncertain and variable scenarios and risks, where human behavior may increase the probability of error. We often have to make short term decisions when attending two patients simultaneously – mother and fetus-, and the mother expects a deferential treatment during pregnancy, delivery and the puerperium. These processes involve multiple activities and tasks, and failures may occur. Faced with the paradigm change of involving the patient in the care and decision making process, we have to provide them with the most complete evidence, to avoid contingencies and to obtain the best possible results.